2019
DOI: 10.1097/ico.0000000000002080
|View full text |Cite
|
Sign up to set email alerts
|

Clinical Characteristics and Outcomes of Ocular Cicatricial Pemphigoid: A Cohort Study and Literature Review

Abstract: Purpose: Ocular cicatricial pemphigoid (OCP) is a rare systemic autoimmune disease and a potentially blinding subepithelial blistering disorder. The purpose of this study was to describe the clinical spectrum of the disease and to assess the efficacy and safety of immunosuppressive agents in a cohort of patients with OCP. Methods: We conducted a monocentric retrospective cross-sectional cohort study of all unselected consecutive patients diagnosed with … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
27
3

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 17 publications
(32 citation statements)
references
References 25 publications
2
27
3
Order By: Relevance
“…After three months on IMT, 59% of the eyes achieved a complete response. Fremont et al reported a signi cantly lower complete response rate (32%) to the rst line immunosuppressants [4]. Our hypothesis to the hindmost are two-fold.…”
Section: Discussionmentioning
confidence: 62%
See 2 more Smart Citations
“…After three months on IMT, 59% of the eyes achieved a complete response. Fremont et al reported a signi cantly lower complete response rate (32%) to the rst line immunosuppressants [4]. Our hypothesis to the hindmost are two-fold.…”
Section: Discussionmentioning
confidence: 62%
“…A partial response was de ned as a reduction of in ammation by at least one grade, and no response as persistent in ammation. This approach has been previously used by other authors [4,14]. Therapy adverse events were de ned as side effects requiring drug discontinuation, whereas disease recurrence was de ned as new-onset conjunctival in ammation after achieving a complete response.…”
Section: Ommp Managementmentioning
confidence: 99%
See 1 more Smart Citation
“…For the aggressive forms of OCP or treatment failure groups, Rituximab should be considered. [ 8 , 9 ] Despite the effectiveness of systemic immunosuppressant, discontinuation rates vary and poor compliance were still noted in some cases. [ 8 ] In addition, OCP patients are general elderly with an advanced stage by the time of diagnosis.…”
Section: Discussionmentioning
confidence: 99%
“…Although it seems to be sufficient to stop disease evolution, no conclusion can be drawn on the efficacy of topical anti-inflammatory treatment. [ 9 , 10 ] In our patient, systemic immunosuppressive therapy was not used during the perioperative period due to the potential side effects and drug toxicity. Furthermore, we believed that topical ciclosporin and topical prednisolone aid in alleviating the conjunctival inflammation and shrinkage.…”
Section: Discussionmentioning
confidence: 99%